Inequality, hunger, and malnutrition: Power matters - Hossain, Naomi (International Food Policy Research Institute, 2017)
The uneven distribution of hunger and nutrition reflects the unequal distribution of power in the food system. In its hourglass shape, the power at the center amplifies poverty and marginalization at both ends of the system: at one end, small-scale farmers and low-paid food producers suffer hardship; at the other end, those excluded from or adversely incorporated into globalized food markets face hunger and malnutrition. Transnational corporations’ growing control over what we eat—which often deepens existing inequalities—has generated a wide range of spaces and forms of resistance. Power analysis encourages us to look beyond the obvious and the measurable, to trace the effects of interests operating at multiple levels of the food system, to find opportunities where and when they arise, and to enter spaces where that power can be challenged, resisted, and redistributed. Achieving the Sustainable Development Goals’ aim of “leaving no one behind” demands approaches to hunger and malnutrition that are both more sensitive to their uneven distribution and more attuned to the power inequalities that amplify the effects of poverty and marginalization in all forms of malnutrition.